Navigation Design and Library Terminology: Findings from a User-Centered Usability Study on a Library Website - Vargas Ochoa, Isabel (Information Technology and Libraries, 2020)
The University Library at California State University, Stanislaus is not only undergoing a library building renovation, but a website redesign as well. The library conducted a user-centered usability study to collect data in order to best lead the library website “renovation.” A prototype was created to assess an audience-based navigation design, homepage content framework, and heading terminology. The usability study consisted of 38 student participants. It was determined that a topic-based navigation design will be implemented instead of an audience-based navigation, a search-all search box will be integrated, and the headings and menu links will be modified to avoid ambiguous library terminology. Further research on different navigation and content designs, and usability design approaches, will be explored for future studies.